Successful dimension for evaluating leadership management in Islamic university - Fu’adi, Athok; Sugiyono, Sugiyono; Prasojo, Lantip Diat (Institute of Advanced Engineering and Science, 2024)
This research aims to test the dimensions of success in measuring leadership management and to find the factors that shape leadership in an excellent Islamic university (IU). Respondents totaled 422 participants from leaders and lecturers at six Islamic universities in Indonesia. partial least squares structural equation modeling (PLS-SEM) analysis is used to test 8 dimensions, 35 constructs, and 17 hypotheses. Management leadership is determined by the dominant factor, namely job evaluation (IM4, λ=90.70%), and human resources (OR3, λ=74.40%) is the lowest factor. The ability of the structural model to explain the measurement of IU’s leadership management is 79.70%. Furthermore, the 17 hypotheses from 8 dimensions have a positive and significant influence. Measurable dimensions can be used to develop an effective management model to increase the performance and function of leadership. Through the results of this research, higher education management institutions can recommend study substances to comprehensively find out the leadership model to be applied by leaders so they are more skilled and expert in managing institutions in higher education.